Temperature- and density-dependent channel potentials in high-mobility organic field-effect transistors - Kemerink, Martijn; Hallam, Toby; Lee, MiJung; Zhao, Ni; Caironi, M.; Sirringhaus, Henning (Physical review. B, Condensed matter and materials physics, 2009)
The density-dependent charge-carrier mobility in high-mobility organic field-effect transistors is investigated by simultaneous measurements of the channel potential and the transfer characteristics. By working under ultrahigh-vacuum conditions extrinsic effects due to H2O traces could be eliminated. The shape of the channel potential is inconsistent with a density-independent mobility. We find that the variable range hopping model as derived by Vissenberg and Matters for an exponential density of states [Phys. Rev. B 57, 12964 (1998)] consistently describes the data.